3D modelling and simulation of heat transfers in the building envelope for different local construction materials in the littoral area of Cameroon. (15th October 2020) - Njamen, Adeline Chugoua; Monkam, Louis; Kemajou, Alexis; Ngouem, Félix Junior; Ngamaleu, Christian Leumassi
The building structure is a filter that controls the heat exchanges between the exterior and the interior of the building. It plays an important role for the thermal comfort of the residents and the energy consumption of the building. The objective of this work is to analyse the thermal behaviour of the building structure in humid climates for various local building materials: wood, cinder block and clay brick. To achieve this, a numerical code was written in the MATLAB 2014a software to solve by the finite difference method implicit scheme, the three-dimensional heat transfer equation. The simulation of our dynamic model takes into account the convection on the external and internal surfaces as well as the diffusion in the material constituting the structure. The particularity of this study is that in addition to being a 3D model, it allows to appreciate the behaviour in the thermal bridges and in the interior geometric centre. After analysis, we recommended an envelope made of wood material in the littoral region.